International Business Law : Text, Cases, and Readings - August, Ray (Jala Permata, 2009)
This textbook is designed for undergraduate and graduate students majoring in business or related disciplines. This text will give students from many cultures and traditions a good look at the overall structure of the legal environment for global business, and may also serve as a useful introduction and refrence to business people and legal practitioners who need an effective overview of nation-to-nation relations, multinational enterprises, dispute settlement across national borders, and rules for global trade in goods and services. International Business Law provides a comprehensive look at critical issues and functions in the global legal environment. Business today is truly international.